2019
DOI: 10.3389/fncel.2019.00375
|View full text |Cite
|
Sign up to set email alerts
|

Mode-Dependent Effect of Xenon Inhalation on Kainic Acid-Induced Status Epilepticus in Rats

Abstract: Previous studies have reported the possible neuroprotective effects of xenon treatment. The purpose of this study was to define the range of effective xenon ratio, most effective xenon ratio, and time-window for intervention in the kainic acid (KA) – induced status epilepticus (SE) rat model. Different ratios of xenon (35% xenon, 21% oxygen, 44% nitrogen, 50% xenon, 21% oxygen, 29% nitrogen, 70% xenon, 21% oxygen, and 9% nitrogen) were used to treat the KA-induced SE. Our results confirmed the anti-seizure rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated the strong xenon neuroprotective effects (Metaxa et al, 2014 ; Lavaur et al, 2016a , b ; Zhang et al, 2019a , b ); however, the possible xenon neuroprotective effects and the underlying mechanisms in seizure-induced neuronal injury remain clear. In this study, we assessed the effects of xenon treatment on neuronal injury; moreover, we evaluated the role of autophagy in KA-induced acute generalized seizures and the involved xenon neuroprotective effects.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have demonstrated the strong xenon neuroprotective effects (Metaxa et al, 2014 ; Lavaur et al, 2016a , b ; Zhang et al, 2019a , b ); however, the possible xenon neuroprotective effects and the underlying mechanisms in seizure-induced neuronal injury remain clear. In this study, we assessed the effects of xenon treatment on neuronal injury; moreover, we evaluated the role of autophagy in KA-induced acute generalized seizures and the involved xenon neuroprotective effects.…”
Section: Discussionmentioning
confidence: 98%
“…Coronal slices (10 μm) were obtained using a cryostat microtome (CM3050s, Leica, Germany). As previously described (Zhang et al, 2019a , b ), we performed the staining procedure (three slices/rat) as per the kit manufacturer’s instructions (AG310, Millipore, USA). Finally, the stained slices were examined under a fluorescent microscope with a 450 nm excitation light (Carl Zeiss AG, Germany), and the number of positive FJB signals (300 × 300 μm vision) in changed subregions was determined and analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG was recorded after sub-FS. After rats were anesthetized and immobilized, the stainless steel electrodes (0.5 mm tips uncoated; A.M. Systems, USA) were implanted into the left cortex [anteroposterior (AP), -2.3 mm; mediolateral (ML), -2.1 mm; dorsoventral (DV), -1.3 mm] for EEG recording in accordance with brain atlases (the third section) [ 79 ]. Subsequently, when the pups woke, the EEG of each animal was continuously recorded for 3 h using a Powerlab device (1-80 Hz, AD Instruments, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, EEG recording and analysis were performed 2 months after PFS. At 53 days after initial PFS, the rats were anaesthetized with pentobarbital sodium (50 mg/kg, intraperitoneally, CAS, 57–33-0, Xiya Reagent, China), and stainless steel electrodes (0.5 mm tips uncoated; A.M. Systems, USA) were implanted into the left cortex ( Zhang et al, 2019b ) using a stereotactic apparatus (Anhui Zheng Hua Biological Instrument Equipment Co., Ltd., China). In accordance with brain atlases (the third section), the electrodes were implanted [anteroposterior (AP), -3.2 mm; mediolateral (ML), -3.0 mm; dorsoventral (DV), -1.8 mm] for EEG recording.…”
Section: Methodsmentioning
confidence: 99%